When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.
3
2
[(x+3)^2] - [(x+2)^2] = 13 ==> 2x = 8 ==> x = 4. the number is 4!
This is equivalent to (x + 3)2 = (x + 2)2 + 9. Multiplied out this is x2 + 6x + 9 = x2 + 4x + 4 + 9. Deduct x2 + 4x + 9 from each side giving 2x = 4 So x = 2 Check: (2 + 3) squared = 25 which is 9 more than (2 + 2) squared = 16.
When the sum of a number plus 3 is squared, it is 11 more than the sum of the number plus 2 when squared.
3
4
2
2
4
4
2
If you mean: (x+3) squared = (x+2) squared +11 Then the value of x works out as 3
a number equals 2
if it is not this . -3<x<-2 < or equal
Are you asking me to tell you the answer? Because its easy and simple .